2010
DOI: 10.2807/ese.15.49.19741-en
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of 2009 pandemic influenza A(H1N1) in Germany

Abstract: The mortality in Germany caused by the 2009 pandemic influenza A(H1N1) seems to have been one of the lowest in Europe. We provide a detailed analysis of all 252 fatal cases of confirmed infection with the pandemic virus notified between 29 April 2009 and 31 March 2010. The overall mortality was 3.1 (95% confidence interval (CI): 2.7 to 3.5) per one million inhabitants. We observed an increase in the case fatality rate of notified cases over time; notified cases aged 60 years or older had the highest case fatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 16 publications
7
60
0
18
Order By: Relevance
“…Further, factors such as diabetes [11], obesity [10] and age [12] which are poor prognostic indicators in symptomatic pandemic H1N1 influenza infection were not associated with asymptomatic carrier state in our study (Table 2). In fact none of the patient characteristics were significantly associated with having asymptomatic carrier state (Table 2).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Further, factors such as diabetes [11], obesity [10] and age [12] which are poor prognostic indicators in symptomatic pandemic H1N1 influenza infection were not associated with asymptomatic carrier state in our study (Table 2). In fact none of the patient characteristics were significantly associated with having asymptomatic carrier state (Table 2).…”
Section: Discussionmentioning
confidence: 50%
“…Then uni-variate and multi-variate logistic regression analysis was performed using presence of H1N1 infection as the dependent variable and age, gender, BMI, diabetes diagnosis, and HbA1C% as independent variables. Since obesity [10] and diabetes mellitus [11] are known to be poor prognostic factors with symptomatic pandemic influenza infection, we included these variables in the logistic regression model to look for their association with asymptomatic carrier state. Though we planned Cox regression on the 4 weeks follow-up data, we could not perform these as none of the participants who were positive at baseline developed respiratory disease during 4 weeks of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada it was also shown that 22.6-38% of the critically ill were or had been smokers [11,14]. In California in 2009, 41% of fatal influenza cases had chronic lung disease [10] while in Germany it was reported to be 23.1% [15].…”
Section: Factors Associated With Death or Hospitalisationmentioning
confidence: 99%
“…In Canada it was also shown that 22.6-38% of the critically ill were or had been smokers [11,14]. In California in 2009, 41% of fatal influenza cases had chronic lung disease [10] while in Germany it was reported to be 23.1% [15].Obesity: Obesity has commonly been reported in ICU submissions and patients dying from pdm(H1N1)09 [6,11,12,[15][16][17][18] …”
mentioning
confidence: 99%
See 1 more Smart Citation